Tinjauan Yuridis Perlindungan Hukum Terhadap Justice Collaborator di Dalam Tindak Pidana Narkotika - I Made Rauhimas Oka Raharja; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Analogi Hukum, 2024)
Narcotics abuse is a very complex problem, as evidenced by the increasing use of narcotics in Indonesia every year. In the criminal justice process, one of the pieces of evidence based on Article 184 paragraph (1) of the Criminal Procedure Code is witness testimony. The presence of witnesses is an important factor. The term witness is now evolving to include Justice Collaborator. The formulation of the problem in this research is How is the arrangement of Justice Collaborators in the criminal law system in Indonesia?and How is the protection of witnesses who work together (justice collaborators) in narcotics crimes according to Law Number 31 of 2014? This study uses a type of normative legal research. The results of the study found a Justice Collaborator. However, the arrangements regarding perpetrator witnesses are considered to be very minimal and do not provide clear guidelines regarding the prerequisites for being able to designate someone as a Justice Collaborator. The role of an actor who is used as a witness in the existing regulations is only known in Article 10 paragraph (2) of Law Number 13 of 2006 in conjunction with Law Number 31 of 2014. Law enforcers in providing legal protection to Justice Collaborators are still guided by Law Number 31 of 2014 Concerning the Protection of Witnesses and Victims, Supreme Court Circular Letter Number 04 of 2011 Concerning the Treatment of Whistleblowers and the witness of the perpetrator (Justice Collaborator). The rules for the existence of the Justice Collaborator are only briefly discussed. Legal protection is also less clear and firm.